Global attractor of an impulsive parabolic system - Perestyuk, M.O.; Kapustyan, O.V.; Romaniuk, I.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
We study the existence of global attractors for impulsive multivalued dynamical systems, which have trajectories with infinite number of impulsive perturbations. The results are applied to a weakly nonlinear parabolic impulsive system.